Peningkatan Profesionalisme Guru Melalui Pengawas Madrasah - Imron Muttaqin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
The aims ofthis studyare; 1) to describe process of planning to increase the professionalism of teachersled by the madrasah supervisors, 2) implementation, and3) Evaluation of improving the professionalism teachers supervised by madrasah supervisors. The results of this study showed that; 1) the planning process started by the coordinating and meeting team work of supervisor, the determination of the object and the review of the instruments of supervision, 2) the improving of teachers proffessionalism implemented with visiting to the madrasah, lesson planning supervision, learning administration, assessment and supervision for guidance and counseling, workshop and technical guidance, 3) professionalism of teachers evaluated with supervision instruments and Performance Evaluation of Teachers (PKG) instruments.